Análisis de procesos psíquicos y culturales y su aplicación en el aprendizaje de una segunda lengua. - Montealegre, Rosalía; Domínguez, María Elvia (Acta Colombiana de Psicología, 1999)
In order to set out the apllication of psychological and cultural process in learning a second language from the perspective of an identity narrative construction. It is necessary start looking different aspects such as: language psychic activity, the instrument and cultural sign conception, the importantce of memory, meaning, speech and gesture. Learning a second language involves a subjective multiple transformation process in relationship with the cognitive, affective, pragmastic and communicative fields. In first place is necessary the assimilation of: scientific and daily concepts, thought patterns, cultural forms of behavior (linguistic, social, logic and mnemonic). Second, the construction of meanings and the narrative recreation of each person. Third, the apllication of comprehensive language models in order to use speech and writing efficiently. Finally, the second language speaker should compenétrate with the cultural narrative and the particular forms of individual communication without rest value to his or hers original culture.